Surgical Cytoreduction and HITOC for Thymic Malignancies with Pleural Dissemination - Markowiak, Till; Neu, Reiner; Ansari, Mohammed Khalid Afeen; Großer, Christian; Klinkhammer-Schalke, Monika; Hofmann, Hans-Stefan; Ried, Michael (The Thoracic and Cardiovascular Surgeon, 2019)
Background Objective of this study was to assess postoperative morbidity and mortality as well as recurrence-free and overall survival in patients with thymic malignancies and pleural dissemination undergoing surgical cytoreduction and hyperthermic intrathoracic chemotherapy (HITOC).Methods Retrospective study between September 2008 and December 2017 with follow-up analysis in May 2018.Results A total of 29 patients (male: n = 17) with thymic malignancies and pleural spread (primary stage IVa: n = 11; pleural recurrence: n = 18) were included. Surgical cytoreduction was performed via pleurectomy/decortication (P/D; n = 11), extended P/D (n = 15), and extrapleural pneumonectomy (EPP; n = 3). These procedures resulted in 25 (86%) patients with macroscopically complete (R0/R1) resection. Intraoperative HITOC was performed for 60 minutes at 42°C either with cisplatin (100 mg/m2 body surface area [BSA] n = 8; 150 mg/m2 BSA n = 6; 175 mg/m2 BSA n = 1) or with a combination of cisplatin (175 mg/m2 BSA)/doxorubicin (65 mg; n = 14). Postoperative complications occurred in nine patients (31%). Cytoprotective therapy resulted in lower postoperative creatinine levels (p = 0.036), and there was no need for temporary dialysis in these patients. The 90-day mortality rate was 3.4%, as one patient developed multiple organ failure. While recurrence-free 5-year survival was 54%, an overall 5-year survival rate of 80.1% was observed. Survival depended on histological subtype (p = 0.01).Conclusion Surgical cytoreduction with HITOC is feasible in selected patients and offers encouraging survival rates. The application of cytoprotective agents appears to be effective for the prevention of postoperative renal insufficiency.
Keywords: tumor; thymus; surgery; complications; pleural disease